Analysis Students Perceptions FEB UNM Management of Cash Withdrawal Transactions Without ATM Cards via the BRImo Application - Anwar (Abadi Institute, 2024)
This study aims to analyze the perceptions of students of the Faculty of Economics and Business (FEB) of Makassar State University (UNM) towards the use of cardless cash withdrawal transactions using the BRImo application. Along with the development of financial technology, various innovations in digital banking services continue to emerge. One of them is the cardless cash withdrawal feature introduced by Bank Rakyat Indonesia (BRI) through the BRImo application. This feature allows users to make cash withdrawal transactions via mobile phones without the need for a physical card, which provides convenience and efficiency. This study uses a quantitative approach with a survey method to collect data from FEB UNM Management students. The results of the study are expected to provide an overview of the acceptance and challenges faced by students in using the service